IDENTIFIKASI PERILAKU, PERSEPSI, DAN MOTIVASI WISATAWAN BERKUNJUNG KE BANYUWANGI SERTA PENGARUHNYA TERHADAP PEMBERDAYAAN MASYARAKAT - Satriyo, Galih; Bastian, Yusron (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
This study aims to analyze tourist behaviour, perceptions, motivation to visit, and satisfaction towards Banyuwangi tourism and its impact on community empowerment. This is a qualitative descriptive study using snowball sampling to collect research data. Research informants were the Culture & Tourism Office officer, an officer of the Cooperative, Medium Business, &Trade Office, 87 tourists, 4 guides, 11 micro-business actors, and 4 Local Tourism Awareness Group representatives. Results showed that most tourists visited Banyuwangi to see Ijen's blue fire, Alas Purwo, & local customs. They gained information from word of mouth, the Internet, & social media. Most tourists perceived that Banyuwangi tourism has good transportation facilities, supporting infrastructure, and accessibility with an affordable entry ticket. The primary motivations to visit Banyuwangi were to escape the routine, gathering with family & friends, increasing local culture knowledge, enjoying sports facilities, and adventure. Most tourists were satisfied & would like to revisit Banyuwangi & recommend it to others. In the last five years, Banyuwangi tourism shows significant developments. It has a positive effect on the community, especially for micro-business entrepreneurs. Keywords: community empowerment, motivation, perception, tourist behaviour